Equilibrium And Kinetic Studies On Biosorption Of Cr (Vi) By Non-Living Mycelial Suspensions Of Aspergillus Niger - I.REYA ISSAC; M. LAKSHMI PRABHA (International Journal of Pharma and Bio Sciences, 2011)
Equilibrium and kinetic studies on biosorption of chromium (VI) from aqueous solution was studied using the dead biomass of Aspergillus niger (A. niger) as a feasible biosorbent under batch method at 300C. Various sorption parameters such as contact time, initial concentration of chromium (VI) ion, effect of pH and effect of biosorbent dosages were studied. The adsorbent was effective for the quantitative removal of chromium (VI) ions in acidic conditions and equilibrium has been achieved in 240 min with a maximum removal of 90% is achieved at pH 2.0. The equilibrium adsorption data were fitted to Langmuir, Freundlich and Dubinin-Radushkevich (DR) adsorption isotherm models and the parameters were evaluated. The kinetic study showed that the first order, second order rate equation and power function equations were studied. Comparatively first order and second order kinetic equations are better described for this biosorption process. This method is found to be quite promising, feasible, economic and time saving.